Relationship Of Strategic Thinking Dimensions Of Administrative Leaders In The Iraqi National Olympic Committee And Sports Federations Central (Journal of the College of Basic Education, 2022)
The interaction of two variables to form a conceptual framework and philosophical for this study, namely, (strategic thinking and organizational culture), has launched the study of the problem is expressed in the formation of the launch of a shift towards strategic thinking, leadership and establish an organizational culture of the institution sports appropriate management strategy for a modern liberated actually the old traditional and is working to rebuild the functions and roles of leadership Sports on the foundations of modern science, and through the interaction of the dimensions of the strategic thinking minds Sports conscious goals, paths are drawn organizational culture compatible with the future direction of the Sports Foundation and supporting excellence and excellence in performance at both the administrative and sports. In addition, the variables surveyed in the study of modern subjects on the Arab environment in general, and the Iraqi environment in particular, and then test the correlations and the impact and the possibility of its implementation in the field of sports, especially in the National Olympic Committee of Iraq and their unions Sports Central, has identified the study sample B (50) individuals. The importance of this study lies in that it will emerge Btaesel the intellectual philosophical nature of the variables of the study, a document to an applied voltage to the reality of the strategic thinking and the organizational culture. To achieve this, the main hypothesis formulated, accepted and tested set of tools nonparametric statistical questionnaire was used as a tool to collect data and information from the study sample.